Switching between laser‐induced thermophoresis and thermal convection of liquid suspension in a microgap with variable dimension. Issue 21 (26th July 2021) - Tsuji, Tetsuro; Taguchi, Satoshi; Takamatsu, Hiroki
Abstract: Phoretic motion of particles along a temperature gradient formed in a fluid, known as thermophoresis, often takes place under the influence of bulk motion caused by thermal convection. In this paper, using a laser heating method, the significance of two competing effects, that is, thermophoresis and thermal convection, for the particle transport in a liquid phase confined in a microgap is investigated experimentally by changing the gap size as a control parameter. It is found that there is a threshold of the gap size, above which the particles tend to accumulate around the heated spot, forming a ring‐like particle distribution. On the contrary, if the gap size is below the threshold, the particles are depleted from the heated spot. Switching between these accumulation and depletion modes is expected to develop novel manipulation techniques.